Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/sj.ejcn.1600612
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose spiral computed tomography for measuring abdominal fat volume and distribution in a clinical setting

Abstract: Objectives: Computed tomography (CT) has been used to measure body composition, however, a technique with reduced radiation exposure has not yet been introduced. This study tested a low-dose spiral CT technique on a phantom to determine its validity and reproducibility. The method was then applied for volume and distribution measurements in patients. Design: Construction and measurement of a phantom followed by measurement of patients referred to CT for clinical indications. Setting: Radiology Department, Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…This difference in the CT number distribution for VAT compared with the other two AT compartments could be attributable to the effect of partial volume averaging, which is partly due to blood vessels within pixels, and differences in biological properties between AT compartment, including differences in the fat fraction of AT, blood flow, and glucose metabolism [14,23,24]. This observation agreed with a previous report [25].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This difference in the CT number distribution for VAT compared with the other two AT compartments could be attributable to the effect of partial volume averaging, which is partly due to blood vessels within pixels, and differences in biological properties between AT compartment, including differences in the fat fraction of AT, blood flow, and glucose metabolism [14,23,24]. This observation agreed with a previous report [25].…”
Section: Discussionsupporting
confidence: 82%
“…Theoretically, X-ray tube voltage by different scanner type may affect the CT number for particular tissues owing to different linear attenuation coefficients, but tube current does not affect CT number for particular tissue, although low-dose scanning used in the current study increases image noise as described in a previous phantom study [25]. The clinical significance of using slightly different tube voltage in measuring total AT volume is questionable.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In 1998, it was clarified by using low-dose helical CT technique in 24 post-gastrectomy subjects comprising nine women and 15 men with a mean age of 60 y, that percentage fat and percentage subcutaneous fat were significantly greater in women than was percentage intra-abdominal fat in men. 5 However, they did not study the correlation between fat volumes by helical CT vs those respective areas measured using conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, however, there had been no study that applied this technique to the measurement of body fat mass. Rogalla et al 5 reported with low-dose helical CT in 24 post-gastrectomy patients that percentage fat and percentage subcutaneous fat were significantly larger in women, as were percentage intra-abdominal and mediastinal fat in men.…”
Section: Introductionmentioning
confidence: 99%